Analisa Metodologi Tafsir Al-Quran Berbasis Ormas di Indonesia Perspektif Metodologi Islah Gusmian - Nurun Najmatul Ulya; Ahmad Yasir Amrulloh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This article examines Indonesian commentary books compiled by Indonesian Community Organizations (ORMAS) or their representatives, namely Tafsir Al-Wa'ie Selected Verses by Hizbut Tahrir Indonesia and Tafsir At-Tanwir by Majlis Tarjih and Tajdid PP Muhammadiyah. The type of research method is library research, because the source of the analysis is based on library data, namely the work of interpretation by the two ORMAS and the formulation of the methodology developed by Islah Gusmian,